Pengaruh Kecerdasan Emosional Dan Motivasi Belajar Terhadap Hasil Belajar IPS Siswa Kelas IX Di UPTD SMP Negeri 4 Pematang Siantar T.P 2023/2024 - Sonia Tamba; Herlina Hotmadinar Sianipar; Sotarduga Sihombing (JOURNAL SAINS STUDENT RESEARCH, 2023)
The research results show that: 1) there is a positive and significant influence of emotional intelligence on student learning outcomes. This result can be seen in the t test where the calculated t value of emotional intelligence is 5.93 > t table value 1.660, which means this variable is significant. 2) there is a positive and significant influence of learning motivation on student learning outcomes. This result can be seen in the t test where the calculated t value of learning motivation is 5.60 > t table value 1.660, which means this variable is significant. 3) emotional intelligence and learning motivation together influence student learning outcomes. This result can be seen in the F test where the calculated F value is 123.06 > F table value 1.6107. The coefficient of determination test was found to be 0.25, which means that 25% of the emotional intelligence and learning motivation variables influence the social studies learning outcomes of class IX students at UPTD SMP Negeri 4 Pematang Siantar.